2020
DOI: 10.1257/aeri.20190385
|View full text |Cite
|
Sign up to set email alerts
|

Rage against the Machines: Labor-Saving Technology and Unrest in Industrializing England

Abstract: Can new technology cause social instability and unrest? We examine the famous “Captain Swing” riots in 1830s England. Newly collected data on threshing machine diffusion shows that labor-saving technology was associated with more riots. We instrument technology adoption with the share of heavy soils in a parish: IV estimates demonstrate that threshing machines were an important cause of unrest. Where alternative employment opportunities softened the blow of new technology, there was less rioting. Conversely, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 22 publications
0
27
1
Order By: Relevance
“…We build on their insights by initially seeking to establish a causal link from new technology to protests and then by showing how context mattered in determining who would go on strike. While Caprettini and Voth (2020) find that protests were amplified where workers were impoverished or had few alternative employment opportunities, our study finds that conflicts following electrification were offensive rather than defensive and were particularly frequent in sectors with increasing demand for labor. Contrary to the rebellions driven by "technological anxiety" observed in the nineteenth century, we argue that the strikes in early twentieth-century Sweden were manifestations of workers' improved bargaining positions due to new labor market conditions.…”
contrasting
confidence: 67%
See 1 more Smart Citation
“…We build on their insights by initially seeking to establish a causal link from new technology to protests and then by showing how context mattered in determining who would go on strike. While Caprettini and Voth (2020) find that protests were amplified where workers were impoverished or had few alternative employment opportunities, our study finds that conflicts following electrification were offensive rather than defensive and were particularly frequent in sectors with increasing demand for labor. Contrary to the rebellions driven by "technological anxiety" observed in the nineteenth century, we argue that the strikes in early twentieth-century Sweden were manifestations of workers' improved bargaining positions due to new labor market conditions.…”
contrasting
confidence: 67%
“…While we study industrial unrest, we draw inspiration from a study of pre-industrial protests. Caprettini and Voth (2020) have convincingly shown that technological change really was at the root of the unrest associated with the Captain Swing riots in 1830s England. By exploiting instrumental variable techniques, they establish a causal link from the 2 See Enflo and Karlsson (2019) and Molinder, Enflo, and Karlsson (2018).…”
mentioning
confidence: 99%
“…Olzak, Shanahan and McEneaney (1996) and Olzak and Shanahan (2003) show that ethnic competition was a primary driver of riots in the United States, and Dancygier (2010) highlights the interaction between economic scarcity and political power in determining the incidence of immigrant riots in the United Kingdom. 6 In the context of the Swing riots, Caprettini and Voth (2020) have shown that the adoption of the threshing machine, a form of labor-saving technology, was an important factor in determining whether a parish experienced riots.…”
Section: Motivationmentioning
confidence: 99%
“…Their money wages were 75d per week in 1770, 276d in 1805 (the peak year) but were back to 75d by 1830 (Wood, 1910). In another well-known episode, the 'Captain Swing' riots (1830-2), the evidence is that these were a response to the diffusion of threshing labour-saving threshing machines which wiped out winter earnings for many agricultural labourers (Caprettini and Voth, 2020).…”
Section: Discussionmentioning
confidence: 99%